(untitled) (Eurasian Medical Research Periodical, 2022)
According to the results of the research, it was revealed that chronic tonsillitis is very common among schoolchildren both in the city and in the countryside. Pathology of hearing loss among schoolchildren in the city is in second place, and among schoolchildren in the village - in third place. This may be due to the high medical care of the population in the city. Chronic otitis among schoolchildren in urban conditions is in third place, and in rural areas - in second place. This is due to the incomplete observance of the hygienic conditions of schoolchildren in rural areas. There were no differences in the incidence of chronic laryngitis and pharyngitis at the place of residence.